URGENSI KURIKULUM PENDIDIKAN KEBENCANAAN BERBASIS KEARIFAN LOKAL DI INDONESIA - Mirza Desfandi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2014)
This article was written to give an idea of the urgency of disaster education curriculum based on local wisdom in Indonesia. For that purpose, the author uses the method of literature. As a country which has enormous potential for disaster, Indonesia needs to implement a disaster curriculum in educational institutions so that students have the knowledge and insight about the disaster. This disaster education have a common goal to provide an overview and reference in the learning process of disaster preparedness. Through education students are expected to be able to think and act fast, precise, and accurate in the face of disaster. Empathy toward victims can also be constructed so that learners can help others appropriately and carefully. Pattern and diversity of natural disasters faced also vary because each region has different characteristics as well. Then, disaster curriculum should accommodate local wisdom, as an effort to provide appropriate education to deal simultaneously with a disaster. Curriculum based on local wisdom will explain the relationship between humans and the natural environment and cultural environment around them.